Identifikasi Karakteristik Kawasan Ekowisata Mangrove Kuala Kota Singkawang - Queentera Cantika Arasanda; Erni Yuniarti; Firsta Rekayasa Hernovianty (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2022)
The geographical condition of Singkawang City located in a coastal area provides opportunities for the development of natural potential. One of them is the development of conservation-based coastal ecotourism through mangroves. However, the development of coastal ecotourism also has several problems. One of coastal ecotourism's threats is the hydro-oceanographic process factors that can erode the surface of the beach floor, human activities such as near the coast, taking natural coastal protectors, converting mangroves into massive fish ponds and logging mangroves. However, in Kuala Subdistrict, West Singkawang District, there is a mangrove forest that is developed by the community through POKDARWIS Pesona Kuala Pesisir. It's just that in its implementation, there are still some problems causing the development of ecotourism is not fully optimized. Through this research, the author focuses on tourism objects in the Kuala Mangrove Ecotourism Area spatially with descriptive analysis. The results of the identification research on tourism objects, the characteristics of the Kuala Mangrove Ecotourism Area consist of four object substances, facilities, objects of attraction, accessibility, and land cover.